G87(P) Audit: Identifying child safeguarding concerns in adults presenting to the emergency department with mental health issues. (24th May 2017) - Pocknell, S; Luck, J; Nocton, S; Shute, J; Dennehy, J; Hann, G
Abstract : Aims: To assess awareness of child safeguarding issues among Emergency Department (ED) staff when assessing adult patients presenting with the 'toxic trio' of mental health issues +/domestic violence and substance misuse. Methods: 98 adults who attended the ED, between 7th – 20th March 2016, with mental health issues were included. ED medical records were analysed for the following information: Was the patient seen by an ED doctor or nurse, or mental health team member, and asked about: social historyresponsibilities for children known to social services substance misuse self harm domestic violence Was the patient discussed with A and E senior/paediatrician/ safeguarding team Was a referral made to social services 'Proformalyse' and 'Rio' databases were checked, to see if the above questions were asked by the mental health team, and whether the patient was known to mental health services. The safeguarding team reviewed referrals received during this period to determine if any corresponded to this data set. Results: All of the patients in this data set present with one of the 'toxic trio': mental health issues. 25% also had substance misuse or domestic violence issues. 19% of patients were asked a social history by an ED doctor, compared with 40% of the patients seen by the mental health team. Only 11% of patients were directly asked by ED staff if they had children, compared with 44% of patients asked by the mental health team. 2% of patients were asked about social services. Five ED records noted a referral to social services was to be made. Only one of these five referrals was found by the safeguarding team on their database. Conclusion: Few adults in ED presenting with one or more of the 'toxic trio' are asked about responsibilities for children, despite a written policy. We are currently missing a large number of potential child safeguarding issues in adult ED. We plan to amend the ED mental health triage proforma to include questions relevant to child safeguarding.